NbEXPA1, an α‐expansin, is plasmodesmata‐specific and a novel host factor for potyviral infection. (17th November 2017) - Park, Sang‐Ho; Li, Fangfang; Renaud, Justin; Shen, Wentao; Li, Yinzi; Guo, Lihua; Cui, Hongguang; Sumarah, Mark; Wang, Aiming
Summary: Plasmodesmata (PD), unique to the plant kingdom, are structurally complex microchannels that cross the cell wall to establish symplastic communication between neighbouring cells. Viral intercellular movement occurs through PD. To better understand the involvement of PD in viral infection, we conducted a quantitative proteomic study on the PD‐enriched fraction from Nicotiana benthamiana leaves in response to infection by Turnip mosaic virus (TuMV). We report the identification of a total of 1070 PD protein candidates, of which 100 (≥2‐fold increase) and 48 (≥2‐fold reduction) are significantly differentially accumulated in the PD‐enriched fraction, when compared with protein levels in the corresponding healthy control. Among the differentially accumulated PD protein candidates, we show that an α‐expansin designated NbEXPA1, a cell wall loosening protein, is PD‐specific. TuMV infection downregulates NbEXPA1 mRNA expression and protein accumulation. We further demonstrate that NbEXPA1 is recruited to the viral replication complex via the interaction with NIb, the only RNA‐dependent RNA polymerase of TuMV. Silencing of NbEXPA1 inhibits plant growth and TuMV infection, whereas overexpression of NbEXPA1 promotes viral replication and intercellular movement. These data suggest that NbEXPA1 is a host factor for potyviral infection. This study not only generates a PD‐proteome dataset that is useful in future studies to expound PD biology and PD‐mediated virus–host interactions but also characterizes NbEXPA1 as the first PD‐specific cell wall loosening protein and its essential role in potyviral infection. Significance Statement: A cell wall loosening protein, α‐expansin in Nicotiana benthamiana which is designated NbEXPA1, is PD‐specific. NbEXPA1 is differentially accumulated upon potyviral infection and plays essential roles in promoting viral replication and intercellular movement.